A platform ecosystem view of servitization in manufacturing. (December 2022) - Kapoor, Kawaljeet; Bigdeli, Ali Ziaee; Schroeder, Andreas; Baines, Tim
Abstract: This study investigates how the social and technical subsystems of a platform ecosystem change and interact in the advanced services context. An integrated research approach results in the development of an analytical framework accounting for the four perspectives of - technical core, key actors, structural boundaries and tasks of a servitization-based platform ecosystem. This study draws from collective experiences of 14 senior executives from seven manufacturing firms using a multiple case study approach. We find that manufacturers' decision to modularise or standardise affects the range of services they can offer, and while modularity presents challenges of engagement between ecosystem actors, standardisation is harder for manufacturers with intricate products and complex customer settings. We also find that complexities of service transformation can trigger product-biased behaviour of internal actors, risking the success of servitization within the organisation. Additionally, we find that manufacturers can concurrently operate across multiple structural boundaries, and this impacts the mechanisms they adopt to govern and orchestrate their actor networks. Highlights: Platform ecosystem lens clarifies servitization-related organisational transformation. Socio-technical components explain functional dynamics of service platform ecosystems. Manufacturers use their products as platforms for achieving their servitization goals.